2017
DOI: 10.1103/physrevx.7.021044
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Implications of Laser-Induced Raman Scattering at Astronomical Observatories

Abstract: Laser guide stars employed at astronomical observatories provide artificial wavefront reference sources to help correct (in part) the impact of atmospheric turbulence on astrophysical observations. Following the recent commissioning of the 4 Laser Guide Star Facility (4LGSF) on the Unit Telescope 4 (UT4) of the Very Large Telescope (VLT), we characterize the spectral signature of the uplink beams from the 22 W lasers to assess the impact of laser scattering from the 4LGSF on science observations. We use the Mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 83 publications
2
31
0
Order By: Relevance
“…The possible presence of wind along the lineof-sight (and thus the spectral shifting of the signal over time) implies that the Raman lines are not suitable to characterize the goal precision of 10 cm s −1 over 10 years for radial velocity measurements with ESPRESSO. We find, however, that the accuracy with which the Raman lines (<5 fm for the case of 16 1 3 3 5 5 7 7 9 9 11 11 12 12 13 13 14 14 16 16 18 18 20 20 22 22 24 24 26 26…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The possible presence of wind along the lineof-sight (and thus the spectral shifting of the signal over time) implies that the Raman lines are not suitable to characterize the goal precision of 10 cm s −1 over 10 years for radial velocity measurements with ESPRESSO. We find, however, that the accuracy with which the Raman lines (<5 fm for the case of 16 1 3 3 5 5 7 7 9 9 11 11 12 12 13 13 14 14 16 16 18 18 20 20 22 22 24 24 26 26…”
Section: Discussionmentioning
confidence: 70%
“…We link the majority of these fainter lines to the existence of a non-zero electronic spin in the ground state 3 Σ − g of 16 O 2 . It is the interaction between this electronic spin and the molecular rotation that leads to the fine-splitting of the pure rotational Raman lines of 16 [32][33][34][35], we can successfully identify side-lines up to N = 9 (where N denotes the end-over-end rotation). We are left with 6 lines of (yet) unknown origin, all located within 13Å from the main laser line (see Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The main parameters of the LGS systems of VLT, ELT, GTC and TMT used for this study are reported in Table 1 together with their closest distance to CTA telescopes and altitude differences. Based on the experience with the 4 Laser Guide Star Facility (4LGSF) on Unit Telescope 4 (UT4) of the VLT (Vogt et al 2017), an LGS system will be implemented on the ELT (Fusco et al 2010), which will rely on continuous wave lasers similar to those of the 4LGSF (according to the current design) . The TMT will operate six lasers, each with a power of 22 W (16.5 W after exiting the beam transfer optics) (Herriot et al 2014).…”
Section: Computation Of Ao-laser Induced Light On Neighbouring Instalmentioning
confidence: 99%